Health-related quality of life by race, ethnicity, and country of origin among cancer survivors - Reeve, Bryce B; Graves, Kristi D; Lin, Li; Potosky, Arnold L; Ahn, Jaeil; Henke, Debra M; Pan, Wei; Fall-Dickson, Jane M (JNCI : Journal of the National Cancer Institute, 2023)
Typical cancer research studies of health-related quality of life (HRQOL) in the United States do not include country of origin when examining race and ethnic group differences. This population-based, cross-sectional study used an innovative methodology to examine how self-reported racial and ethnic groups, by country of origin, report differential HRQOL experiences after adjusting for clinical and demographic characteristics, including socioeconomic status. Recruited from 4 cancer registries in California, Louisiana, and New Jersey, cancer survivors completed Patient-Reported Outcomes Measurement Information System measures of fatigue, pain interference, anxiety, depression, sleep disturbance, physical function, ability to participate in social roles, and cognitive function. Latent profile analysis clustered survivors in HRQOL clusters based on including all the Patient-Reported Outcomes Measurement Information System domains. The 5366 participants (60% female; 40% male; average age of 59.8 years) included 17% Asian, 18% Black, 21% Hispanic, and 41% White survivors. Survivors were grouped into 4 clusters: high HRQOL (26%), average HRQOL (34%), low HRQOL (29%), and very low HRQOL (11%). Among many differences by race, ethnicity, and country of origin, Caribbean cancer survivors were more likely to be in the very low HRQOL cluster (odds ratio = 2.67, 95% confidence interval = 1.31 to 5.43) compared with non-Hispanic White survivors. Similarly, American Indian and Alaska Native, Cuban, Dominican, and Puerto Rican cancer survivors had relatively high percentages in the very low HRQOL cluster. This study found statistically significant differences in HRQOL experience by race, ethnicity, and country of origin, even after adjusting for social determinants of health. These findings inform future HRQOL research to include these self-reported factors.